Intermediate age Galactic open clusters: fundamental parameters of NGC 2627 - Piatti, Andres Eduardo (2003)
Charge-coupled device (CCD) photometry in the Johnson V, Kron–Cousins I and Washington CMT1 systems is presented in the field of the poorly known open cluster NGC 2627. Four independent Washington abundance indices yield a mean cluster metallicity of [Fe/H] = −0.12 ± 0.08, which is compatible with the existence of a radial gradient in the Galactic disc. The resultant colour–magnitude diagrams indicate that the cluster is an intermediate-age object of 1.4 Gyr. Based on the best fits of the Geneva group’s isochrones to the (V, V − I) and (T 1, C − T 1) diagrams, we estimate E(V − I) = 0.25 ± 0.05 and V − MV = 11.80 ± 0.25 for log t = 9.15, and E(C − T 1) = 0.23 ± 0.07 and T 1−MT 1 = 11.85 ± 0.25 for log t = 9.10, respectively, assuming solar metal content. The derived reddening value E(C − T 1) implies E(B − V) = 0.12 ± 0.07 and a distance from the Sun of 2.0 ± 0.4 kpc. Using the WEBDA data base and the available literature, we re-examined the overall properties of all the open clusters with ages between 0.6 and 2.5 Gyr. We identified peaks of cluster formation at 0.7–0.8, 1.0–1.1, 1.6–1.7 and 2.0–2.1 Gyr, separated by relative quiescent epochs of ∼0.2–0.3 Gyr. We also estimated a radial abundance gradient of −0.08 ± 0.02, which is consistent with the most recent determinations for the Galactic disc, but no clear evidence for a gradient perpendicular to the Galactic plane is found.